Simultaneous Optimization for Multiple Responses on the Compression Moulding Parameters of Composite Graphite–Polypropylene Using Taguchi Method - Selamat, Mohd zulkefli; Sahari, Jaafar; Muhamad, Norhamidi; Muchtar, Andanastuti (Trans Tech Publications Ltd, Switzerland, 2011)
This research concerns the effect of compression molding parameters on conducting polymer composite (CPC) properties such as electrical conductivity and flexural strength. In the present work on CPC, focus is given to graphite (G) as filler and polypropylene (PP) was use as the binder. The Taguchi’s L9 orthogonal array has been used as design of experiment (DOE) while the electrical conductivity and flexural strength were assumed to be quality characteristic (responses). The electrical conductivity was measured using four point probes and flexural strength was measured using three point tests according to ASTM D638. Classical analysis of variance (ANOVA) was used to investigate the significant of each compression molding parameters and finally propose the optimum compression molding parameters. But for several responses, the optimum condition for one response is not very likely to the optimum condition for other response.